Method for coating hygroscopic catalyst particles to prevent water adsorption - Patents.com

JP2024501745A5Pending Publication Date: 2025-01-09SAUDI ARABIAN OIL CO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023540794
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-01-04
Filing Date
2022-01-03
Publication Date
2025-01-09

AI Technical Summary

Technical Problem

Hydroprocessing catalysts are hygroscopic, leading to water adsorption that results in mass increase and activity loss, especially when exposed to air, which affects their performance.

Method used

Catalyst particles are coated with a paraffinic wax or polymer coating material to prevent water adsorption, ensuring they remain non-absorbent during hydroprocessing.

Benefits of technology

The coating process maintains catalytic activity by preventing water adsorption, thereby enhancing the catalyst's performance and stability during use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

To prevent water adsorption onto the catalyst particles, the non-absorbing presulfided catalyst particles are provided coated with a suitable coating material, such as paraffinic oil / wax, or a suitable polymeric material.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a catalyst for the hydroprocessing of petroleum and petroleum fractions and a method for preparing the catalyst. [Background technology]

[0002] Hydroprocessing (hydrotreating and hydrocracking) catalysts can be prepared by various methods. The method chosen usually represents a balance between the cost of production and the degree to which the desired chemical and physical properties are achieved. There is a relationship between catalyst formulation, preparation procedure, and catalyst properties, but the details of that relationship are not always fully understood due to the complex nature of the catalyst systems. The chemical composition of the catalyst plays an important role in its performance; the physical and mechanical properties also play a major role. The preparation of hydrocracking catalysts involves several steps: precipitation, filtration (decantation, centrifugation), washing, drying, shaping, calcination, and impregnation. Other steps, such as kneading or blending, grinding, and sieving, may also be required. Depending on the preparation method used, some of these steps may be omitted, while others may be added. For example, blending or co-blending of wet solid precursors is used in some processes instead of impregnation. If the metal precursor is co-precipitated or co-blended with the support precursor, the impregnation step can be omitted. The steps which are an integral part of the hydrocracking catalyst manufacturing process are described below.

[0003] Hydroprocessing catalysts are hygroscopic and will adsorb water when exposed to air. Water adsorption results in several disadvantages for the catalyst, such as mass gain, activity loss, etc. After being placed in the reactor, the hydroprocessing catalyst is sulfided to convert the active phase metals from the oxide form to the sulfide form. Hydroprocessing catalysts are also provided in a presulfided form by the catalyst manufacturer, and the catalyst is often activated with hydrogen. However, it has been reported that the activity of the sulfided catalyst decreases when it is exposed to air (FE Massoth, C.-S. Kim, Jian-W. Cui, "Studies of molybdena-alumina catalysts: XVII. Sulfided catalysts exposed to air", Applied Catalysis, Vol. 58, No. 1, February 5, 1990, pp. 199-208).

[0004] FIG. 1 shows a typical catalyst manufacturing process, for example for producing hydroprocessing catalysts. Hydroprocessing catalysts refer to those used for hydrodesulfurization, hydrodenitrogenation, hydrocracking, hydrodewaxing, hydrogenation, and / or hydrodemetallization. In a particular implementation, the hydroprocessing catalyst is composed of one or more active components impregnated on a support material. The support material components are provided in steps 102, 104. In step 102, a binder material is provided, and in step 104, an active catalyst support material, such as a zeolite, is provided. The support material components are mixed and kneaded in step 106. Precipitation involves mixing of a solution or suspension of materials, which results in the formation of a precipitate, which may be crystalline or amorphous. Kneading or kneading of the wet solid materials usually results in the formation of a dough, which is then shaped and dried. The kneaded or blended product is subjected to heat treatment to obtain closer contact and better homogeneity between the components by thermal diffusion and solid-state reaction. Precipitation or kneading is often used to prepare supports for catalysts, and the metal components are then added by impregnation, for example using the incipient wetness method.

[0005] The characteristics of the support determine the mechanical properties of the catalyst, such as attrition resistance, hardness, and crush strength. High surface area and suitable pore size distribution are generally required. The pore size distribution and other physical properties of catalyst supports prepared by precipitation are also influenced by the precipitation and aging conditions of the precipitate, as well as by the subsequent drying, shaping, and calcination.

[0006] The final shape and size of the catalyst particles are determined during the manufacturing process. Examples of catalyst and catalyst support shapes are shown in FIG. 2. Catalysts and catalyst supports are formed into several possible shapes, such as spheres 202, cylindrical extrudates 204, or shaped forms, such as trilobes 206 or quadrilobes 208. Spherical catalyst support catalysts can be obtained by "oil dripping", whereby precipitation occurs when a liquid is poured into a second immiscible liquid. Other sphericity processes include marmelizing. In general, due to process considerations such as cost and pressure drop, the majority of catalysts are currently formed into shapes other than spheres. Fewer spherical catalysts are used in modern hydrocracking.

[0007] In step 108, the non-spherical shape is obtained by mixing the raw materials to form an extrudable dough, which is extruded through a die with holes. The spaghetti-like extrudates are dried, calcined and broken into short pieces. The typical ratio of length to diameter of the catalyst substrate varies, for example, between 2 and 4. The simplest form is a cylindrical particle, but other forms, such as trilobe, twisted trilobe or quadrilobe, are also used commercially. Catalysts with multilobe cross-sections have a higher surface-to-volume ratio than simple cylindrical extrudates. When used in fixed beds, these shaped catalyst particles help to lower the diffusion resistance, create a more open bed and reduce the pressure drop.

[0008] In step 110, the support particles are heat treated and calcined. Heat treatment can be applied either before and / or after impregnation of the shaped catalyst. For catalysts prepared by precipitation or co-kneading of all components (including metal components), only drying may be required before shaping, followed by calcining the shaped product. Heat treatment of the catalyst or support eliminates water and other volatiles; calcination also serves to decompose impregnated metal salts, including decomposition of nitrates, chlorides, carbonates and organic chelates, leaving metals or metal oxides on the support surface. Drying and calcination conditions are very important in determining the physical properties of the product as well as the catalytic properties. Surface area, pore size distribution, stability, attrition resistance, crush strength, and catalytic activity are affected by drying and calcination conditions.

[0009] In step 112, active metals are added to the calcined support material, which is commonly referred to as impregnation. Several methods can be used to add active metals to the substrate: (a) immersion (dipping), (b) incipient wetness, and (c) evaporation. In the most commonly used method, the calcined support is immersed in an excess of solution containing the active metal or metal compound. The solution fills the pores and is adsorbed onto the support surface, and the excess solution is removed. In another method, impregnation is performed using incipient wetness by tumbling or spraying the activated support with a solution having a concentration of metal compound adjusted to achieve the targeted metal level in a volume equal to or slightly less than the pore volume of the support. The metal-loaded support is then dried and calcined, step 114. Metal oxides are formed in this process; the calcination step is also referred to as oxidation. In another method, evaporation impregnation, the support is saturated with water or an acid solution and immersed in an aqueous solution containing the metal compound. The compound then diffuses through the aqueous phase into the pores of the support.

[0010] The final catalyst product after calcination is bagged and shipped to its final destination in step 116. Some catalysts, especially those containing zeolites, are hygroscopic and therefore will adsorb water after calcination, e.g., during shipping, and prior to use at the final destination. In addition, as described above, the activity of sulfide or oxide catalysts after exposure to air is known to decrease. [Prior art documents] [Patent documents]

[0011] [Patent Document 1] U.S. Patent No. 9,221,036 [Patent Document 2] U.S. Patent No. 10,081,009 [Patent Document 3] U.S. Patent No. 10,293,332 [Non-patent literature]

[0012] [Non-Patent Document 1] F.E. Massoth, C.-S. Kim, Jian-W. Cui, "Studies of molybdena-alumina catalysts: XVII. Sulfided catalysts exposed to air", Applied Catalysis, Vol. 58, No. 1, February 5, 1990, pp. 199-208. [Non-Patent Document 2] the National Library of Medicine, PubChem (site: https: / / pubchem.ncbi.nlm.nih.gov) [Non-Patent Document 3] Peter Morgan, Analysis of Petroleum Fractions by ASTM D2887, Thermo Fisher Scientific Inc. (2012) (Published AN20582_E 08 / 12S) https: / / static.thermoscientific.com / images / D22163~.pdf [Non-Patent Document 4] https: / / www.engineeringtoolbox.com / hydrocarbon-boiling-melting-flash-autoignition-point-density-gravity-molweight-d_1966.html Summary of the Invention [Problem to be solved by the invention]

[0013] Despite the many advances in hydroprocessing catalysts, the industry is constantly searching for improved catalytic materials, especially those with improved storage properties. [Means for solving the problem]

[0014] The present disclosure relates to a catalyst production method in which catalyst particles are rendered non-sorbent by treatment with a coating material, such as a paraffinic wax, which is decomposed under catalyst activation conditions during operation in a hydroprocessing reactor.

[0015] The process described above is a conventional process. The catalyst after calcination is bagged and transported to its final destination. Some catalysts, especially those containing zeolites, are hygroscopic and will adsorb water after calcination and before final arrival at the site. As described herein, it is known that exposure of sulfide or oxide catalysts to air results in reduced catalytic activity. This problem is overcome by the non-absorbent catalyst particles and the method of making the non-absorbent catalyst particles disclosed herein. These non-absorbent catalyst particles prevent adsorption of water onto the catalyst particles and retain catalytic activity.

[0016] In one embodiment, a method of making a catalyst for use in a catalytic process is provided. An active catalyst support material and a binder material are mixed to form a catalyst support blend. The catalyst support blend is extruded and shaped in an extruder to produce catalyst support particles having an average cross-sectional dimension between about 0.01-3.0 mm. The catalyst support particles are calcined to produce calcined catalyst support particles. One or more active components are incorporated into the calcined catalyst support particles to produce catalyst particles having active components. The catalyst particles having active components are calcined to remove volatile and contaminating materials and produce hygroscopic catalyst particles. The hygroscopic catalyst particles are coated with a coating material to produce non-absorbing catalyst particles.

[0017] In one embodiment, a method of making a catalyst for use in a catalytic process is provided. An active catalyst support material and a binder material are mixed to form a catalyst support blend. The catalyst support blend is extruded and shaped in an extruder to produce catalyst support particles having an average cross-sectional dimension between about 0.01-3.0 mm. The catalyst support particles are calcined to produce calcined catalyst support particles. One or more active components are incorporated into the calcined catalyst support particles to produce catalyst particles having active components. The catalyst particles having active components are calcined to remove volatile and contaminating materials and produce hygroscopic catalyst particles. The hygroscopic catalyst particles are presulfided to produce presulfided hygroscopic catalyst particles. The presulfided hygroscopic catalyst particles are coated with a coating material to produce non-absorbing presulfided catalyst particles.

[0018] In certain embodiments, the active catalyst support material comprises a zeolite, hi certain embodiments, the binder material comprises a metal oxide.

[0019] In certain embodiments, the coating material is a paraffinic wax having a carbon number ranging from 31 to 50. In certain embodiments, the coating material is an n-paraffinic wax. In certain embodiments, the coating material is dissolved in a paraffinic or aromatic solvent having a carbon number ranging from 5 to 7, such as pentane, hexane, benzene, toluene, or naphtha boiling in the range of 36 to 100° C. In certain embodiments, the coating material is a polymer or mixture of polymers derived from olefins, carbonates, aromatics, sulfones, fluorinated hydrocarbons, chlorinated hydrocarbons, or acrylonitriles.

[0020] In certain embodiments, the coating material is sprayed onto the hygroscopic catalyst particles in a batch or continuous manner. In certain embodiments, the coating material is poured onto the hygroscopic catalyst particles. In certain embodiments, the hygroscopic catalyst particles are dipped into the coating material and drained.

[0021] In certain embodiments, the coating occurs at a temperature above the melting point of the coating material and below the boiling point of the coating material. In certain embodiments, the coating occurs at a pressure range of about 1-3 bar. In certain embodiments, the catalyst is cooled to room temperature before being coated.

[0022] A hydroprocessing method is provided that includes using non-adsorbing catalyst particles formed according to any of the above methods, where the non-adsorbing catalyst particles are placed in a reactor and the reactor is heated during start-up to a suitable temperature to remove coating material from the catalyst particles. In certain embodiments, the catalyst particles are sulfided after the coating material has been removed.

[0023] There is provided a non-absorbing catalyst material comprising an active catalyst support material and a binder material formed as an extrudate, together with an active component, wherein the extrudate is encapsulated with a coating material comprising an n-paraffinic wax having a carbon number in the range of 31 to 50 or a polymer having a melting point in the range of 83 to 327°C.

[0024] Further other aspects, embodiments, and advantages of these exemplary aspects and embodiments are discussed in detail below. Moreover, it should be understood that both the preceding information and the following detailed description are merely illustrative examples of the various aspects and embodiments, and are intended to provide an overview or framework for understanding the nature and characteristics of the claimed aspects and embodiments. The accompanying drawings are included to provide illustrations and a further understanding of the various aspects and embodiments, and are incorporated in and constitute a part of this specification. The drawings, together with the rest of the specification, serve to explain the principles and implementation of the described and claimed aspects and embodiments.

[0025] The present invention will be described in further detail below and with reference to the accompanying drawings, in which like or similar elements will be referred to by like numerals, in which: [Brief description of the drawings]

[0026] [Figure 1] FIG. 1 is a schematic diagram of a process for conventional production of a catalyst product that is hygroscopic; [Diagram 2] 1 shows examples of catalyst particle shapes; [Diagram 3] 1 is a schematic diagram of a process for the production of a non-absorbing catalyst product; [Figure 4] FIG. 1 is a schematic diagram of a process for the production of a non-absorbing presulfided catalyst product; [Diagram 5] 1 is a graph showing the melting and boiling points of n-paraffinic waxes used in embodiments herein for the production of non-absorbing catalyst products; [Figure 6] 1 is a graph showing the composition of n-paraffinic waxes used to coat catalyst particles in the examples; [Figure 7] FIG. 1 shows environmental scanning electron microscopy (ESEM) topography images along with energy dispersive (EDS) spectra of paraffin-coated catalyst samples; and [Figure 8]1 is a graph showing the results of thermogravimetric analysis of paraffin-coated catalyst samples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0027] In this method, the catalyst particles are coated with a suitable coating material, such as paraffinic oil / wax, or a suitable polymeric material, to prevent water adsorption onto the catalyst particles. Figure 3 is a schematic diagram of an embodiment of a process for producing a non-absorbing catalyst product by including a coating step. Figure 4 is a schematic diagram of an embodiment of a process for producing a non-absorbing pre-sulfided catalyst product.

[0028] FIG. 3 is a schematic diagram of a process for producing non-sorbing catalyst particles for use as hydroprocessing catalysts. The steps for forming the hygroscopic catalyst particles are similar to those described herein with respect to FIG. 1, including mixing 106 an active catalyst support 104 and a binder 102, extruding 108 the blend in an extruder to form catalyst support particles having an average cross-sectional dimension, for example, between about 0.01-3.0 mm, calcining 110 the catalyst support particles, impregnating 112 the catalyst support particles with an active phase metal, and calcining 114 the impregnated catalyst particles to remove volatiles and other contaminants. After calcination, the catalyst particles are free or substantially free of water (e.g., less than about 0.05 or 0.005 W %). The particles are cooled, for example to room temperature, and in step 120 the hygroscopic impregnated catalyst particles are coated with a coating agent to form the final non-sorbing catalyst particles 122. The coating material is removed from the catalyst particles during reactor start-up, e.g., before sulfidation occurs. After the coating material is removed, the catalyst may be sulfided at start-up, as known in the art.

[0029] Figure 4 is a schematic diagram of a process for producing presulfided non-absorbing catalyst particles for use as hydroprocessing catalysts. The steps for forming the hygroscopic catalyst particles are similar to those described herein with respect to Figure 1, including mixing 106 an active catalyst support 104 and a binder 102, extruding 108 the blend in an extruder to form catalyst support particles having an average cross-sectional dimension, for example, between about 0.01-3.0 mm, calcining 110 the catalyst support particles, impregnating 112 the catalyst support particles with an active phase metal, and calcining 114 the impregnated catalyst particles to remove volatiles and other contaminants. Additionally, in step 128, the calcined impregnated catalyst particles are presulfided. After calcination and presulfiding, the catalyst particles are free or substantially free of water (e.g., less than about 0.05 or 0.005 W %). The particles are cooled, e.g., to room temperature, and in step 130, the hygroscopic presulfided impregnated catalyst particles are coated with a coating agent to form the final non-sorbing presulfided catalyst particles 132. The coating material is removed from the catalyst particles during reactor start-up, e.g., without additional sulfiding or before additional sulfiding occurs. In certain embodiments, after the coating material is removed, the presulfided catalyst may be further sulfided during start-up.

[0030] The catalyst particles suitable for the coating process disclosed herein include at least one or more binder materials and at least one or more active support materials. Examples of binder materials include alumina, silica, titania, silica-alumina, alumina-titania, alumina-zirconia, alumina-boria, phosphorus-alumina, silica-alumina-boria, phosphorus-alumina-boria, phosphorus-alumina-silica, silica-alumina-titania, and silica-alumina-zirconia. Active support materials include zeolitic materials, including but not limited to zeolites with medium or large pore sizes. Examples include, for example, mordenite, ZSM-5, ZSM-11, ZSM-12, ZSM-22, ZSM-23, ZSM 35, and beta and Y-type zeolites.

[0031] The active metal component or components carried on the support material are metals or metal compounds (oxides or sulfides) selected from IUPAC Groups 6, 7, 8, 9 and 10 of the Periodic Table of Elements. In certain embodiments, the active metal component is one or more of Mo, W, Co or Ni. The active metal component is typically deposited or otherwise incorporated on the support, such as amorphous alumina, amorphous silica-alumina, zeolite, or combinations thereof. The active metal component is incorporated in an effective concentration, for example, in the range of 1-40, 1-30, 1-10, 1-5, 2-40, 2-30, 2-10, 3-40, 3-30 or 3-10 (W% based on the weight of oxide, sulfide or metal to the total weight of catalyst). In certain embodiments, Pt group metals, such as Pt and / or Pd, alone or in combination with the above metals, may be present as the hydrogenation component, typically in an amount of about 0.1-2 W% based on the weight of the catalyst.

[0032] In certain embodiments, the catalyst particles have a pore volume in the range of about (cc / gm) 0.15-1.70, 0.15-1.50, 0.30-1.50, or 0.30-1.70, about (m 2 / g) 100 to 900, 100 to 500, 100 to 450, 180 to 900, 180 to 500, 180 to 450, 200 to 900, 200 to 500 or 200 to 450, and an average pore diameter of at least about 45, 50, 100, 200, 500 or 1000 Angstrom units.

[0033] The coating material is selected such that it can be made into a liquid for the coating process described herein and can be removed during the start-up period when the coated catalyst is placed in the reactor. In the coating process, the coating material is heated in a vessel and liquefied at an appropriate temperature and pressure. The temperature and pressure conditions for the coating process are selected such that the coating material is in the liquid phase to maximize contact with the surface of the catalyst particles. These coating conditions are below the boiling point of the selected coating material to avoid vaporization of the selected coating material during the coating process.

[0034] During the coating process, the coating material can be provided as a pure substance or in solution. In certain embodiments, the coating material is dissolved in a suitable solvent that is effective to contain the coating material in solution and also capable of being removed during the coating process. The coating material solution in the solvent can contain any suitable amount of coating material, for example, 0.1-100, 0.1-99, 0.1-90, 0.1-80, 0.1-70, 0.1-60, 0.1-50, 0.1-25, 0.1-10, 0.1-5, 1-100, 1-99, 1-90, 1-80, 1-70, 1-60, 1-50, 1-25, 1-10, 1-5, 5-100, 5-99, 5-90, 5-80, 5-70, 5-60, 5-50, 5-25, or 5-10 W % of the coating material.

[0035] In certain embodiments, the coating material (i.e., the material remaining on the catalyst particles after coating) is a heavy paraffin or a mixture containing one or more heavy paraffins having a carbon number in the range of 31-50 ("C31-C50 paraffin"). In further embodiments, the coating material comprises a mixture containing one or more C31-C50 heavy paraffins and one or more paraffinic waxes having a lower carbon number, such as in the range of 15-30, 16-30, 17-30, 18-30, or 19-30. In embodiments using heavy paraffinic coating materials, lighter paraffinic or aromatic solvents (preferably free of contaminants) may be used. For example, such solvents may have a carbon number in the range of 5-7, and may include, for example, one or more of pentane, hexane, benzene, toluene, or mixtures thereof. In certain embodiments, naphtha or a light naphtha fraction (preferably hydrotreated), for example boiling in the range of about 36-100° C., may be used.

[0036] In further embodiments, the coating material is a polymer or mixture of polymers derived, for example, from olefins, carbonates, aromatics, sulfones, fluorinated hydrocarbons, chlorinated hydrocarbons, and / or acrylonitriles. In embodiments using polymeric coating materials, suitable solvents include acetone, or methanol for acrylonitriles.

[0037] In embodiments where the coating material is used without a solvent, the temperature and pressure conditions for the coating process are related to the melting and boiling points of the coating material or coating material composition. The pressure typically ranges from atmospheric pressure (e.g., about 1 bar) to about 3 bar. The temperature is above the melting point and below the boiling point of the individual coating materials. In mixtures of coating materials, these are based on the composition of the mixture, for example using the highest melting point and lowest boiling point of the range of components. Table 1 shows the properties of certain n-alkanes. Table 2 shows the properties of certain polymers. In embodiments where the coating occurs in the absence of a solvent, the coating is carried out at a temperature above the melting point of the highest melting material that is intended to remain as part of the coating material on the finished coated catalyst to be transported. In addition, the maximum temperature during the coating process should not exceed the boiling point of the lowest boiling component of the coating mixture that is intended to remain as part of the coating material on the finished coated catalyst to be transported (as opposed to the solvent, carrier, or other components that are not intended to be retained as part of the coating material on the finished coated catalyst). For example, in embodiments where the range of intended components on the finished coated catalyst ranges from C19 to C50, the minimum coating temperature is at least about 92° C. and the maximum coating temperature is no greater than about 331° C. In embodiments where the intended components of the finished coated catalyst are dissolved in a solvent during the coating process, the coating material solution is initially in the liquid phase and a lower temperature can be used for coating; the coating process temperature and pressure conditions are selected such that the coating material remains in the liquid phase, so that it does not precipitate as a solid or vaporize as a gas.

[0038] The amount of coating material provided is sufficient to encapsulate the exterior surface of the catalyst particles. For example, the encapsulating coating thickness can range from about 0.02-0.2, 0.02-0.15, 0.02-0.1, 0.05-0.2, 0.05-0.15, or 0.05-0.1 mm. The catalyst particles should be free or substantially free of dust or powder prior to coating, and if any such contaminants are present, they should be removed prior to coating herein.

[0039] In the coating process, the coating material is heated in a coating material vessel and maintained in a liquefied state under the temperature conditions generally described above. In a solventless coating process, the conditions include a pressure in the range of about 1-3 bar and a temperature in the range of about 30-331, 30-300, 30-250, 30-200, 50-331, 50-300, 50-250, 50-200, 70-331, 70-300, 70-250, or 70-200° C. In a solventless coating process, the conditions include a pressure in the range of about 1-3 bar and a temperature in the range of about 15-80, 15-50, 15-30, 20-80, 20-50, 20-30, 25-80, 25-50, or 25-30° C. The temperature and pressure of the coating material vessel should be well below the temperature and pressure of vaporization or decomposition of the coating material. In certain embodiments, the liquefied coating material or coating material solution is sprayed onto the catalyst particles, for example by one or more suitable nozzles. In certain embodiments, for example in a batch process, a tray of catalyst particles can be sprayed with the liquefied coating material or coating material solution. In further embodiments, for example in a continuous process, the catalyst particles can be traversed, for example using a conveyor belt, so that they can be sprayed with the liquefied coating material or coating material. Excess coating material can be collected and recycled back to the coating material vessel for reuse. In other embodiments, the liquefied coating material or coating material solution is poured onto the catalyst particles. In another embodiment, the catalyst particles are immersed in the liquefied coating material or coating material solution and then drained.

[0040] The temperature of the coating material should be such that the coating material dries as soon as the particles are separated from the liquid. The residence time of the particles in the liquid coating material should be sufficient for the coating material to encapsulate the catalyst particles and should range from 1 to 60 or 1 to 30 seconds. To minimize the use of coating material and the mass of the catalyst, multiple layers should be avoided.

[0041] In certain embodiments, the removal during start-up includes melting the coating material from the catalyst particles, and thus the selection of coating materials or coating material mixtures includes those having melting points in the range of the reactor start-up temperature. For example, the coated catalyst is placed in a reactor and the temperature is increased (e.g., from room temperature) to the final reactor operating temperature. For example, if C50 paraffin, which has a melting point of 92.2°C, is used as all or part of the coating material or coating material mixture, start-up conditions above that temperature are used, e.g., start-up conditions in the range of about 150-500, 200-500, 150-450, 200-450, 150-400, 200-400, 150-360, 200-360, 150-340, or 200-340°C are suitable.

[0042] 5 shows the melting and boiling points of n-paraffinic waxes used in embodiments herein for the production of non-absorbing catalyst products. A suitable range of n-paraffin waxes (carbon numbers 31-50) is shown in the rectangular box; these have high melting points in the range of about 67.9-92° C., which is an effective range for use as a coating material for the catalyst particles described herein because the coating material remains intact and melts easily in the range used during reactor start-up so that the wax can be removed. EXAMPLES

[0043] A hydrocracking catalyst was provided that includes nickel and molybdenum as active phase metals contained in / on a support of an alumina binder and 30 W% Ti-Zr-modified USY zeolite. The Ti-Zr-modified USY zeolite was prepared as disclosed in U.S. Pat. Nos. 9,221,036, 10,081,009 and 10,293,332, which are incorporated herein by reference. The hydrocracking catalyst was dried in an oven at 150° C. for 1 hour to remove any volatile material. A quantity of 5.6 grams of the dried catalyst was added to a wax solution in pentane containing 24 W% wax. The mixture was stirred until all the solvent had evaporated. The final mass of the catalyst was 6.8 grams, which indicates that 1.2 grams of wax was coated on the catalyst particles.

[0044] Figure 6 shows the composition of the coating material used to coat the catalyst particles. The circles in Figure 6 represent the concentration (W%) of n-alkanes in the coating material with the carbon number listed. For example, the wax used contained 13.1 W% N-pentacosane, a paraffin with a carbon number of 25, and 6.6 W% N-triacontane, a paraffin with a carbon number of 30. The triangles represent the cumulative concentration of n-alkanes in the coating material. At room temperature (20°C), all n-alkanes in the mixture are solids.

[0045] FIG. 7 shows an Environmental Scanning Electron Microscopy (ESEM) topography image along with an Energy Dispersive (EDS) spectrum of the paraffin-coated catalyst sample. As can be seen, the catalyst surface is completely covered with paraffin wax. FIG. 8 shows the results of a thermogravimetric analysis of the paraffin-coated catalyst sample. The sample was analyzed using a TGA Q500 (thermal analyzer) instrument. In the TGA method, the sample is weighed and placed in the TGA sample device. To determine the mass loss and remaining mass of the sample, the analysis was performed under air atmosphere at a heating rate of 20° C. / min from 25° C. to 900° C. As can be seen, approximately 19 W% of the material was lost during heating, which corresponds to the approximate percentage of wax on the coated particles (1.2 g wax / total mass of coated catalyst particles 6.8 g). The remaining material is an agglomeration of catalyst particles.

[0046] The method and system of the present invention have been described above and in the accompanying drawings; however, modifications will be apparent to those skilled in the art and the scope of protection for the present invention should be defined by the following claims.

[0047] [Table 1]

[0048] Data are from the National Library of Medicine, PubChem (https: / / pubchem.ncbi.nlm.nih.gov) using values ​​from the source EPA DSSTox, with the exception of n-tetracontane, whose boiling point is taken from Peter Morgan, Analysis of Petroleum Fractions by ASTM D2887, Thermo Fisher Scientific Inc. (2012) (Publication AN20582_E 08 / 12S) https: / / static.thermoscientific.com / images / D22163~.pdf, and melting and boiling point data for n-pentacontane and n-hexacontane from https: / / www.engineeringtoolbox.com / hydrocarbon-boiling-melting-flash-autoignition-point-density-gravity-molweight-d_1966.html.

[0049] [Table 2] [Explanation of symbols]

[0050] 102 Binder 104 Zeolite 106 Mixing and kneading 108 Extrusion 110 Calcination 112 Impregnation 114 Calcination 116 Final catalyst product 120 Coating 122 Final non-absorbed catalyst product 128 Pre-sulfurization 130 Coating 132 Final presulfided non-absorbent catalyst product 202 sphere 204 Cylinder 206 3-lobe (trilobe) 208 4-lobe (Quadrilobe)

Claims

1. A hydroprocessing process for the hydrodesulfurization, hydrodenitrogenation, hydrocracking, hydrodewaxing, hydrogenation, and / or hydrodemetallization of petroleum and petroleum fractions, comprising the steps of: placing non-absorbing catalyst particles comprising zeolite and metal oxide binder material extrudates incorporating an oxidation active metal component selected from the group consisting of Mo, W, and Ni and having less than about 0.05 wt. % water into a reactor, the extrudates being encapsulated with a coating material comprising a mixture containing one or more C31-C50 heavy paraffins and one or more C15-C30 paraffins; and heating the reactor to a temperature in the range of about 150-500° C. during start-up to remove coating material from the catalyst particles; A method comprising:

2. The non-absorbing catalyst particles are mixing the zeolite and the metal oxide binder material to form a catalyst support blend; extruding and shaping the catalyst support blend in an extruder to produce catalyst support particles having an average cross-sectional dimension between about 0.01 and 3.0 mm; calcining the catalyst support particles to form calcined catalyst support particles; incorporating one or more active metal components into the calcined catalyst support particles to produce catalyst particles having active metal components; calcining the catalyst particles having active metal components to remove water, volatile materials and contaminant materials and to oxidize the active metal components to produce hygroscopic catalyst particles having oxidized active metal components thereon and having less than about 0.05 wt. % water; coating the hygroscopic catalyst particles with a coating material to produce non-hygroscopic catalyst particles; The method of claim 1 , wherein the compound is formed by

3. A hydroprocessing process for the hydrodesulfurization, hydrodenitrogenation, hydrocracking, hydrodewaxing, hydrogenation, and / or hydrodemetallization of petroleum and petroleum fractions, comprising the steps of: placing non-absorbing pre-sulfided catalyst particles comprising zeolite and metal oxide binder material extrudates incorporating an oxidation active metal component selected from the group consisting of Mo, W, and Ni and having less than about 0.05 wt. % water into a reactor, the extrudates being encapsulated with a coating material comprising a mixture containing one or more C31-C50 heavy paraffins and one or more C15-C30 paraffins; and heating the reactor to a temperature in the range of about 150-500° C. during start-up to remove coating material from the presulfided catalyst particles; A method comprising:

4. A non-absorbing pre-sulfided catalytic material comprising: mixing the zeolite and the metal oxide binder material to form a catalyst support blend; extruding and shaping the catalyst support blend in an extruder to produce catalyst support particles having an average cross-sectional dimension between about 0.01 and 3.0 mm; calcining the catalyst support particles to form calcined catalyst support particles; incorporating one or more active metal components into the calcined catalyst support particles to produce catalyst particles having active metal components; calcining the catalyst particles having an active component to remove volatile and contaminating materials and produce hygroscopic catalyst particles; presulfiding the hygroscopic catalyst particles to sulfidize the active metal components from the oxide form to the sulfide form to produce presulfided hygroscopic catalyst particles having less than about 0.05 wt. % water; and coating the presulfided hygroscopic catalyst particles with a coating material to produce non-sorbing presulfided catalyst particles; The method of claim 3 , wherein the compound is formed by

5. The method according to any one of claims 1 to 4, wherein the coating material is n-paraffin wax.

6. The method according to claim 3 or 4, wherein the coating material is dissolved in a paraffinic solvent having a carbon number in the range of 5 to 7.

7. The method of claim 6, wherein the paraffinic solvent is pentane, hexane, or naphtha boiling in the range of 36 to 100°C.

8. 5. The method of claim 3 or 4, wherein the coating material is sprayed onto the hygroscopic catalyst particles in a batch or continuous manner.

9. 5. The method of claim 3 or 4, wherein the coating material is poured onto the hygroscopic catalyst particles.

10. 5. The method of claim 3 or 4, wherein the hygroscopic catalyst particles are immersed in the coating material and drained.

11. 5. The method of claim 3 or 4, wherein the coating occurs at a temperature above the melting point of the coating material and below the boiling point of the coating material.

12. The method according to claim 3 or 4, wherein the coating occurs at a pressure in the range of about 1 to 3 bar.

13. The method of claim 3 or 4, wherein the hygroscopic catalyst particles are cooled to room temperature before being coated.

14. The method of claim 1 further comprising the step of sulfiding the catalyst particles after the coating material has been removed.

15. The method of any one of claims 1 to 4, wherein the coating material comprises an n-paraffin wax having a carbon number in the range of 31 to 50.

16. The method according to claim 1, wherein the metal oxide binder is selected from the group consisting of alumina, silica, titania, silica-alumina, alumina-titania, alumina-zirconia, alumina-boria, phosphorus-alumina, silica-alumina-boria, phosphorus-alumina-silica, silica-alumina-titania, and silica-alumina-zirconia, and the zeolite is selected from the group consisting of mordenite, ZSM-5, ZSM-11, ZSM-12, ZSM-22, ZSM-23, ZSM 35, beta zeolite, and Y zeolite.

17. The method of claim 1, wherein the metal oxide binder is selected from the group consisting of alumina, silica, and silica-alumina, and the zeolite is selected from the group consisting of mordenite, ZSM-5, ZSM-11, ZSM-12, ZSM-22, ZSM-23, ZSM 35, beta zeolite, and Y zeolite.